Effects of an intervention to promote competence in the provision of quality care during labour. - Samaranayake, M.D.A (My University, 2007)
Based on the findings of the baseline assessment, an intervention was carried out to I improve knowledge, attitudes and skills of the nurses and midwives in providing intrapartum care. A before-and-after study design was used to evaluate the effects of the intervention. The effectiveness of the intervention on knowledge, attitudes, and skill s was assessed three months alter the interterventlon, using the same instrument an procedure used for the pre-intervention assessment. The sustainability of the effects was assessed six months after the intervention using the same instrument and procedure. Post intervention assessment of maternal satisfaction with care, was conducted at the same time in two different samples of mothers.. Post-intervention results showed a marked improvement in all aspects of care attempted to enhance by the intervention, The total knowledge level showed that significant increase had occurred from 40.9 present ( at pre-intervention stage to 69.2 percent at three months after the intervention, and to 72.1 percent at six months after the intervention respectively. The attitude scores also showed a significant increase from 50.1 percent (at pre-intervention stage to 67.8 percent three months after the intervention and to 70.2 percent at six-months after the invention. Both nurses and midwives in the study showed significant increase in the skills of provision of care. Communication skills had increased from the 31.7 percent pre-intervention level to ( 76.7 percent at three months after the intervention and to 83.3 percent at 6 months after the intervention respectively. Skills in the recording observation on the partogram had increased from the 31.7 percent pre- intervention level to 76.7 percent at three months after the intervention and to 91.7 percent at 6 months after the intervention respectively. Maternal satisfaction with care had increased significantly from 39.9 percent at per intervention stage to 64.9 present at three months after the intervention and to 67.6 percent at six months after the intervention respectively.